Changes in soil nutrient content and bacterial community after 12 years of organic amendment application to a vineyard. (14th May 2015) - Calleja‐Cervantes, M. E.; Menéndez, S.; Fernández‐González, A. J.; Irigoyen, I.; Cibriáin‐Sabalza, J. F.; Toro, N.; Aparicio‐Tejo, P. M.; Fernández‐López, M.
Summary An interesting alternative to landfills for disposing of organic residues is their addition to soil as composted organic residues. There is little information available about the long‐term benefits following prolonged periods of application. After 12 years of annual incorporation of organic amendments to the soil of a vineyard, three soil characteristics were analysed: mineral content, bacterial community and soil greenhouse gas (GHG) emissions. The organic amendments were (i) a pelletized organic compost (PEL) made from plant, animal and sewage sludge residues, (ii) a compost made from the organic fraction of municipal solid waste (OF‐MSW) and (iii) a stabilized sheep manure compost (SMC). Mineral fertilizer (NPK) and an unaltered control treatment were also included. Our results showed that long‐term application of treated residues as compost changed soil nutrient content, bacterial community and gas emission rates. For instance, SMC increased nutrients and soil organic matter (OM) throughout the experiment. There was a change in bacterial community structure, with an increase in the phylum Proteobacteria observed for all four treated soils, and an increase in the phylum Bacteroidetes for PEL, OF‐MSW and SMC treatments. Among the organically‐amended soils, the amount of Adhaeribacter increased by a factor of 2.5 times more than the control, which reported a total of 2.0% of the bacterial community compared with 5.6% for PEL, 5.2% for OF‐MSW and 5.0% for SMC. Adhaeribacter may be a genus that specializes in the degradation of residues in the different composts. The SMC treatment had the largest Chao1 estimator and was the most biodiverse of all treatments. These changes in bacterial community structure did not correlate with the observed GHG fluxes from the sampling day. The application of amendments did not affect N2O fluxes. However, the application of treatments slightly reduced the capacity for CH4 sequestration by soil with respect to the untreated soils. Compost is an effective method to increase soil fertility. Soil GHG emissions should be further evaluated.